Pendidikan Khusus Perempuan: Antara Kesetaraan Gender dan Islam - Erma Pawitasari (Universitas Darussalam Gontor, 2015)
Liberalism and gender equity has influenced the society so much that the different roles between men and women are minimized. Social agreements based on traditions, cultures, and religion are deliberately violated. Women are given opportunity to enter “masculine world”, such as becoming a president or a soldier. Men are given the opportunity to enter “feminine world”, such as becoming a women hair stylist or an OBGYN (a doctor that specializes in women’s reproductive’s health). Everyone is given the freedom to choose their own gender, furthermore, to change their sex organ when they feel comfortable with their choice of gender. Special education based on human’s natural gender is envisaged as discriminative and out dated. Literature research is conducted to understand if special education based on gender is a fruitless idea, if men and women have no unique needs according to their gender differences, and what Islamic perspective is on women education. The finding is an eye-opening. This article shows that brain research reveals a distinguished anatomy and function between male’s and female’s brains. Thus, it is only natural that each gender has unique needs. Further study shows, not only that men and women entail special education to fulfill their distinct needs, divergent methods of teaching are also important to boost both male and female students’ performance.